Multidetector computed tomography diagnosis of adenomyomatosis of the gallbladder - Aysel Türkvatan,; Mehmet Akif TÜRKOĞLU,; Yusuf Alper ÖZOĞUL,; Alper KARACAN,; Musa AKOĞLU, (Turkish Journal of Gastroenterology, 2019)
-